2022
DOI: 10.1590/s1677-5538.ibju.2021.0790
|View full text |Cite
|
Sign up to set email alerts
|

Could urinary nerve growth factor and bladder wall thickness predict the treatment outcome of children with overactive bladder?

Abstract: Objective: Bladder wall thickness (BWTh) measurements and Nerve Growth Factor (NGF) /creatinine (Cr) values, as noninvasive tools, were found to predict daytime voiding problems in children with overactive bladder (OAB). The goal of this research was to examine if bladder wall thickness together with urine NGF/Cr could be a clinical utility in treatment outcome of OAB in children. Patients and Methods: A total of 60 children with OAB, (Group 1; n=40) and healthy normal controls (Group 2; n=20), aged 6-14 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 23 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…The average score was 3.91+/−0.56. The level of evidence was found as B for 13 (81.25%) articles 9–14,16–18,20,22–24 and C for 3 (18.75%) articles 15,19,21 …”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…The average score was 3.91+/−0.56. The level of evidence was found as B for 13 (81.25%) articles 9–14,16–18,20,22–24 and C for 3 (18.75%) articles 15,19,21 …”
Section: Resultsmentioning
confidence: 93%
“…In six studies conducted with children with OAB, urinary NGF levels were found to be higher than the control group in five studies. 9,12,16,17,23 Also, one of them showed that urinary NGF values were found to be higher in children with urodynamically proven detrusor overactivity compared to healthy controls. 12 However, in one study, no relationship was found between OAB and urinary NGF levels.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations